Forever Vietnam : How a Divisive War Changed American Public Memory - Kieran, David, 1978- (Book collections on Project MUSE., 2014)
"Kieran focuses his analysis on the recent remembrance of six events, three of which occurred before the Vietnam War and three after. The first group includes the siege of the Alamo in 1836, the incarceration of Union troops at Andersonville during the Civil War, and the experience of American combat troops during World War II. The second comprises the 1993 U.S. intervention in Somalia, the crash of United Airlines Flight 93 on September 11, 2001, and the Iraq and Afghanistan wars."--